IMPLIKATUR DALAM NOVEL API TAUHID KARYA HABIBURRAHMAN EL SHIRAZY - Rachmalina '; Auzar '; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT:  This research discusses Implikatur in the novel fire tauhid the work of Habiburrahman El Shirazy and discusses forms, meanings and violation of the principle of cooperation on the novel of fire tauhid the work of Habiburrahman El Shirazy. This research uses qualitative descriptive method and approach which aims to describe the implikatur what are used in the novel the fire tauhid the work of Habiburrahman El Shirazy. Research results in the form of implikatur, meaning and classification of violations of the principle of cooperation that is found in the novel the fire tauhid the work of Habiburrahman El Shirazy. The results of this research as well as a form of documentation of the existing Implikatur in the novel fire tauhid the work of Habiburrahman El Shirazy. Keywords: Implikatur, novel fire tauhid the work of Habiburrahman El Shirazy